2020
DOI: 10.3390/ijms21186554
|View full text |Cite
|
Sign up to set email alerts
|

The Antihypertensive Effect of Quercetin in Young Spontaneously Hypertensive Rats; Role of Arachidonic Acid Metabolism

Abstract: Hypertension affects almost 50% of the adult American population. Metabolites of arachidonic acid (AA) in the kidney play an important role in blood pressure regulation. The present study investigates the blood pressure-lowering potential of quercetin (QR), a naturally occurring polyphenol, and examines its correlation to the modulation of AA metabolism. Spontaneously hypertensive rats (SHR) were randomly divided into four groups. Treatment groups were administered QR in drinking water at concentrations of 10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 36 publications
(58 reference statements)
0
29
0
Order By: Relevance
“…The enzymatic activity of rats suggested that medium and high doses of quercetin resisted high blood pressure. They hypothesized that quercetin has anti-hypertensive and provided a novel mechanism for its underlying cardioprotective properties [14]. The protective effects of quercetin against isoproterenol-induced myocardial ischemia and verification of the cellular mechanisms based on the L-type Ca 2+ channel (LTCC), Ca 2+ transients, and myocardial contractility was reported by Liang et al [15].…”
Section: Quercetin As a Cardioprotective Agentmentioning
confidence: 95%
See 1 more Smart Citation
“…The enzymatic activity of rats suggested that medium and high doses of quercetin resisted high blood pressure. They hypothesized that quercetin has anti-hypertensive and provided a novel mechanism for its underlying cardioprotective properties [14]. The protective effects of quercetin against isoproterenol-induced myocardial ischemia and verification of the cellular mechanisms based on the L-type Ca 2+ channel (LTCC), Ca 2+ transients, and myocardial contractility was reported by Liang et al [15].…”
Section: Quercetin As a Cardioprotective Agentmentioning
confidence: 95%
“…Rolnik et al [13] investigated quercetin derivatives for the development of new anti-platelet strategies and management of current therapies in cardiovascular diseases linked to hyper-activation of platelets. Further, Elbarbry et al [14] have elaborated the role of quercetin by studying its role in lowering blood pressure. The effect of quercetin in spontaneously hypertensive rats (SHR) was studied by administrating different concentrations of quercetin.…”
Section: Quercetin As a Cardioprotective Agentmentioning
confidence: 99%
“…Further, quercetin allowed aortic relaxation in SHR by enhancing NO and decreasing the expression of NADPH oxidase in some subunits. Similarly, Elbarbry et al determined the effect of oral administration of quercetin in drinking water (10, 30, and 60 mg/L) on blood pressure and arachidonic acid (AA) metabolism in spontaneously hypertensive rats [ 59 ]. Medium- and high-dose quercetin ameliorated blood pressure in SHR.…”
Section: Flavonols and Their Cardioprotective Activitymentioning
confidence: 99%
“…Medium- and high-dose quercetin ameliorated blood pressure in SHR. Further, by reducing the activity of the key enzymes involved in AA metabolism (cytochrome P450 4A and soluble epoxide hydrolase, sEH), quercetin influenced AA metabolism in the kidney [ 59 ]. Thus, the antihypertensive effects of quercetin may be partially due to its effect on AA metabolism, although the mechanism underlying the improvements in blood pressure by this substance is still unknown.…”
Section: Flavonols and Their Cardioprotective Activitymentioning
confidence: 99%
“…QCT has also been found to have preventive effects in the treatment of cardiovascular diseases and diabetes. Treatment with QCT exerted antihypertensive effects [ 26 ], as well as cardioprotective effects against ischemia-reperfusion (I/R) injury [ 27 , 28 ] or doxorubicin-induced cardiotoxicity [ 14 ]. QCT has also been reported to protect through antioxidant mechanisms against myocardial infarction in streptozotocin (STZ)-induced diabetic rats [ 20 ].…”
Section: Introductionmentioning
confidence: 99%